Materials Science and Materials Chemistry for Large Scale Electrochemical Energy Storage: From Transportation to Electrical Grid. (4th June 2012) - Liu, Jun; Zhang, Ji‐Guang; Yang, Zhenguo; Lemmon, John P.; Imhoff, Carl; Graff, Gordon L.; Li, Liyu; Hu, Jianzhi; Wang, Chongmin; Xiao, Jie; Xia, Gordon; Viswanathan, Vilayanur V.; et al.
Abstract Large‐scale electrical energy storage has become more important than ever for reducing fossil energy consumption in transportation and for the widespread deployment of intermittent renewable energy in electric grid. However, significant challenges exist for its applications. Here, the status and challenges are reviewed from the perspective of materials science and materials chemistry in electrochemical energy storage technologies, such as Li‐ion batteries, sodium (sulfur and metal halide) batteries, Pb‐acid battery, redox flow batteries, and supercapacitors. Perspectives and approaches are introduced for emerging battery designs and new chemistry combinations to reduce the cost of energy storage devices.